Characterization and isolation of microsatellite in Persian sturgeon (Acipenser persicus, Borodine, 1897) - Moghim, Mehdi; Porkazemi, M; Rezvani Gilkolaei, S.; Laloei, F.; Bagherzadeh Afrozi, F.; Yarmohamadi, M; Kor, D.; Nayerani, M; Taghavi, M.J. (Iranian Fisheries Science Research Institute, 2013)
In order to have a sustainable management on Persian sturgeon (Acipenser persicus) as a highly commercial species in the South Caspian Sea, we need to identify its population structure and the level as well as its conservation status in their natural habitat. To develop a conservation program for this all Caspian Sea' sturgeon species it requires knowledge of its genetic diversity using reliable molecular marker to study population genetic structure. For these purposes, an enriched library was prepared based on a modified biotin-capture method. Approximately 1800 positive clones were screened for microsatellites in an Acipenser persicus genomic library. Of these 350 positively hybridizing clones were sequenced, and 81 clones were identified as having microsatellites with adequate flanking regions. We developed and tested 68 microsatellite primer pairs for Persian sturgeon. Out of 68 primer pairs developed, 11 pairs resulted in poor or no amplification, 13 were ambiguous, 6 were monomorphic, 20 were tetrasomic and 18 were octosomic in Persian sturgeon. While none of the markers showed disomic inheritance in Persian sturgeon and Russian sturgeon (A. gueldenstaedtii). Several of the markers appeared useful for studies stellate sturgeon (A. stellatus), ship sturgeon (A.nudiventris) and beluga (Huso huso). Nearly all the polymorphic pattern for ship, stellate and beluga displayed the simple banding patterns characteristic of disomic loci, while those for Russian sturgeon displayed banding patterns characteristic of tetraploid or higher polyploid levels. These markers may prove useful in a variety of future sturgeon population genetic studies in the Caspian Sea.